Shifting sands?: assessing the social inclusion of persons with disabilities in Algiers - Pinto, Paula Campos (2019)
Social inclusion of persons with disabilities has become a pressing issue in Algeria, particularly following the country’s ratification of the Convention on the Rights of Persons with Disabilities (CRPD) in 2009. This paper presents the results of a study that aimed to understand the factors that hinder or facilitate the social inclusion of persons with disabilities in the region of Algiers. The study uses a mixed-methods approach that included a questionnaire (n = 285) and semi-structured interviews (n = 48) applied to persons with disabilities aged 15-45 years in Algiers. Results showed that despite the growing recognition of persons with disabilities rights within the Algerian legal and policy framework, important gaps persist in the implementation of those rights. An extreme economic vulnerability, low educational levels and obstacles to inclusion in the labour market are still evident. Lack of physical accessibility, discrimination against persons with disabilities in the labour market and the persistence of negative attitudes towards persons with disabilities in public services and in society in general (e.g., labelling; staring; lack of respect for priority) are further obstacles reported. This paper discusses the implication of these results for Algeria’s compliance with the norms and principles of the CRPD.